INTEGRATING SIMULATION-BASED LEARNING IN MEDICAL ESP FOR DEVELOPING PROFESSIONAL COMMUNICATIVE COMPETENCE - Davletova Iroda Ulug‘bek qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
English for Medical Purposes (EMP) is a fundamental component of modern medical education, aimed at developing professional communicative competence among future healthcare specialists. In the context of globalized medicine, the ability to communicate effectively in English is essential for clinical practice, academic exchange, and international collaboration. However, traditional language teaching methods often fail to prepare students for real-life medical communication. This study examines the role of simulation-based learning, particularly clinical role-plays, in enhancing speaking skills and professional interaction in Medical ESP classes. The findings demonstrate that simulation-based approaches significantly improve students’ communicative accuracy, fluency, and confidence. The integration of such methods contributes to bridging the gap between theoretical language knowledge and practical medical application.